Reverse logistics for recycling: The customer service - Patrícia Oom do Valle; Joao Menezes; Elizabeth Reis; Efigenio Rebelo (International Journal of Business Science & Applied Management (IJBSAM), 2009)
Customer service is a central concern in the logistics practice and a study topic in the forward logistics research. This article investigates the elements of customer service and their importance in reverse logistics for recycling. Since consumer is the first intervenient in any reverse system that aims to recycle household residues, the provision of an adequate customer service gains an increased importance. Applying multivariate statistical methods (exploratory factor analysis, confirmatory factor analysis and discriminant analysis) to the data from a sample of 267 Portuguese citizens, this study identifies the levels of customer service in this reverse logistics chain and evaluates their relative importance in achieving consumers' participation. The study finds that, as in forward logistics, the customer service in reverse channels for recycling also has a hard and a soft level, being the former more important than the later. The results of this research suggest important guidelines to improve such a complex logistics service.
Keywords: 650; reverse logistics; customer service; multivariate statistics